RANCANGAN PERBAIKAN PENGENDALIAN KUALITAS PADA PRODUK BARU DENGAN PENDEKATAN SIX SIGMA - Ramadhani, Kholid (Arthavidya Jurnal Ilmiah Ekonomi, 2021)
Abstract. This study was aimed to identify cause of defect that occurred in newproducts at automotive - spare part company by designing the right qualitymanagement system with root cause analysis. Qualitative methodology was used,where data and other information collected by interviews, direct observation,document review, and evaluation of reports related to quality achievement. Thecompletion phase of this study was used the DMAIC concept as a corrective action andcontinuous improvement for quality achievement. From analysis result, the factors thatcause defects in new products are differentiated by 11 defect categories. Thedominant defect category was ‘no taping option’ and TBO. The proposed qualitycontrol design to reduce the number of defects are by adding more specific trainingfor new operators according to their own work, adding quality control process byQC after the sub- assembling process, replace all opposite jigs with push pull jigand adding verification tools and other production facilities by the QA-QC departmentKeywords: Quality control system, Six Sigma, DMAIC, defect